2013
DOI: 10.1161/strokeaha.112.677328
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial Cell Transplantation Provides Timing-Dependent Cell Distribution and Functional Recovery After Stroke

Abstract: Background and Purpose-Intra-arterial cell transplantation offers a novel therapeutic strategy for stroke; however, it remains unclear how the timing of cell administration affects cell distribution, brain repair processes, and functional recovery. Here, we investigate the hypothesis that the timing of cell transplantation changes the behavior of the cell graft and the host environment in a way that affects functional recovery. Methods-Rats received human mesenchymal stem cells via the internal carotid artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 38 publications
7
90
0
Order By: Relevance
“…The results showed that IA-transplanted ADMSCs were profoundly found in the host brain in the 1-day group compared with the 3-day and 7-day groups (Supplementary Figure S3). This result is consistent with the study of Ishizaka et al [25], in which IA transplantation of MSCs at 1 day after MCAo induction showed the best engraftment rate in the damaged brain of stroke rats. Therefore, we decided to treat IA transplantation of AD-MSCs at 1 day after MCAo induction in the present study.…”
Section: Intra-arterial Transplantation Of Ad-mscssupporting
confidence: 93%
“…The results showed that IA-transplanted ADMSCs were profoundly found in the host brain in the 1-day group compared with the 3-day and 7-day groups (Supplementary Figure S3). This result is consistent with the study of Ishizaka et al [25], in which IA transplantation of MSCs at 1 day after MCAo induction showed the best engraftment rate in the damaged brain of stroke rats. Therefore, we decided to treat IA transplantation of AD-MSCs at 1 day after MCAo induction in the present study.…”
Section: Intra-arterial Transplantation Of Ad-mscssupporting
confidence: 93%
“…Our data is compatible with the previously published studies which demonstrated that the optimum time for intervention with NSCs was 3 days after ischemic stroke and it is related to diminished inflammatory response after the acute phase and the peak of post-ischemic apoptotic surge (29). A recent study involving intra-arterial delivery of mesenchymal stem cells in a rodent model of MCAO showed that time of cellular intervention drastically impacted the donor cell distribution and functional recovery in the experimental group (38). The authors observed motor functional recovery in the animals which received cell transplantation therapy on day 4 as compared to those treated on day 1 and day 7 after experimental ischemic stroke.…”
Section: Discussionsupporting
confidence: 92%
“…In a subsequent study, the same group tested the effect of human MSCs (hMSCs) injected iv one day after stroke induction in rats and showed that only a few (1 to 5%) hMSCs could be detected in the CNS; this was associated with a decrease in apoptotic cells in the ischemic boundary zone accompanied by an increase in brain-derived neurotrophic factor and nerve growth factor in cerebral tissue, as well as an increase in proliferation of endogenous cells in the subventricular zone [111] More recently, Ishika et al demonstrated that also following intra-arterial hMSC transplantation one or four days after MCAO, functional recovery can be successfully achieved; however, only a few cells could be detected early in the core and in the periinfarct area, associated with a significant decrease of microglia activation, increased number of reactive astrocytes, and enhanced angiogenesis [112]. Similar data were confirmed by many others suggesting that even following intra-arterial administration, MSCs poorly engraft in the brain following cerebral ischemia despite a significant functional recovery [113].…”
Section: Ischemic Strokementioning
confidence: 99%